2021
DOI: 10.1007/s12649-021-01591-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Enhanced Solid–Liquid Separation of Digestate: Suspended Solids Removal and Effects on Environmental Quality of Separated Fractions

Abstract: Chemically enhanced solid–liquid separation (CES) of digestate can improve its membrane filterability but potentially influence the environmental features of the separated solid fraction, thus hindering its possible agricultural reuse. In this study, the effects were assessed of different dosages of polyaluminum chloride (PAC), epichlorohydrine-dimethylamine with ethylendiamine (DEED) and polyacrilamides (PAM) on CES of digestate from biowaste in terms of Total Suspended Solid (TSS) mitigation in the liquid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent research of new types of chemically enhanced solid-liquid separation (CES) treatments indicated that polyaluminum chloride (PAC), epichlorohydrine-dimethylamine with ethylendiamine (DEED) and polyacrilamides (PAM) such as cationic and anionic polyacrylamide (CPAM, APAM respectively) in different ratio had a potential to improve the environmental quality of the solid fraction. The highest Total Suspended Solid (TSS) removal rate (up to 90 ± 1% with respect to the control) in the liquid fractions separated after centrifugation was achieved using PAC4 (3.6 g•L -1 of PAC and 0.2 mg•L -1 of CPAM), PACDE5 (3.2+4.2 g•L -1 of PAC + DE and 0.32 mg•L -1 of APAM) and PACDE6 (3.2+4.2 g•L -1 of PAC + DE and 0.32 mg•L -1 of CPAM) [Beggio et al, 2021]. Besides of this, such treatment provides the predominant transfer of phosphorus and heavy metals (cadmium, lead, copper, nickel, zinc and chromium) into the liquid fraction, regardless of the type of reagent, while organic nitrogen is concentrated in the solid phase.…”
Section: Investigation Of the Dewatering Technologies Of The Digestatementioning
confidence: 99%
“…Recent research of new types of chemically enhanced solid-liquid separation (CES) treatments indicated that polyaluminum chloride (PAC), epichlorohydrine-dimethylamine with ethylendiamine (DEED) and polyacrilamides (PAM) such as cationic and anionic polyacrylamide (CPAM, APAM respectively) in different ratio had a potential to improve the environmental quality of the solid fraction. The highest Total Suspended Solid (TSS) removal rate (up to 90 ± 1% with respect to the control) in the liquid fractions separated after centrifugation was achieved using PAC4 (3.6 g•L -1 of PAC and 0.2 mg•L -1 of CPAM), PACDE5 (3.2+4.2 g•L -1 of PAC + DE and 0.32 mg•L -1 of APAM) and PACDE6 (3.2+4.2 g•L -1 of PAC + DE and 0.32 mg•L -1 of CPAM) [Beggio et al, 2021]. Besides of this, such treatment provides the predominant transfer of phosphorus and heavy metals (cadmium, lead, copper, nickel, zinc and chromium) into the liquid fraction, regardless of the type of reagent, while organic nitrogen is concentrated in the solid phase.…”
Section: Investigation Of the Dewatering Technologies Of The Digestatementioning
confidence: 99%